Selected Abstracts of the 3rd Edition of Transport of High Risk Infants; Oxford (UK); August 31st-September 2nd, 2017 - - (Hygeia Press di Corridori Marinella, 2017)
Selected Abstracts of the 3rd Edition of Transport of High Risk Infants; Oxford (UK); August 31st-September 2nd, 2017 ABS 1. MORTALITY RATE IN 23-30 WEEKS PREMATURE BORN IN LEVEL 2 HOSPITAL IN COMPARISON TO THOSE BORN IN TERTIARY-CARE HOSPITAL • J.P. Doray, J.L. Doray ABS 2. THE QUEBEC AEROMEDICAL EXPERIENCE: EVACUATION OF NEONATES FROM AREAS IN EXTREME WEATHER CONDITIONS - INNOVATIONS IN SAFETY AND EFFICIENCY • É. Notebaert, J. Provencher, R. Bernier, S. Côté, S. Kind ABS 3. NASAL HIGH FLOW SUPPORT DURING NEONATAL RETRIEVAL IN VICTORIA, AUSTRALIA • V. Abraham, C. Roberts, B. Manley, L. Owen, M. Stewart, P. Davis ABS 4. NEONATAL TRANSPORT TO AND FROM A REGIONAL LEVEL 2 CENTRE • C. Moore, M. Cassidy, M. Byrne, A. Bowden, J. Franta, I. Farombi, J. Fitzsimons ABS 5. PASSIVE THERAPEUTIC HYPOTHERMIA DURING AMBULANCE AND HELICOPTER SECONDARY NEONATAL TRANSPORT IN NEONATES WITH HYPOXIC BRAIN INJURY: 10-YEARS RETROSPECTIVE SURVEY • M. Leben, M. Nolimal, I. Vidmar, S. Grosek ABS 6. STABILIZATION OF CRITICALLY ILL NEWBORNS: PREVENTION OF ACUTE KIDNEY INJURY • A. Babintseva, Y. Hodovanets, L. Agafonova ABS 7. TRANSPORT OF THE SURGICAL NEONATES • R. Pejaver, A. Poveidein, D. Winterbank-Scott, C. Keys, N. Gupta ABS 8. AUDIT OF VENTILATED NEONATAL TRANSFERS IN NORTHERN IRELAND FROM 1ST JANUARY 2017 UNTIL 1ST MAY 2017 • R. Moore, S. Knox ABS 9. "HUB AND SPOKE" ECMO IN NEONATES WITH MECONIUM ASPIRATION SYNDROME: A PRELIMINARY REPORT • N. Doglioni, D. Fichera, F. Zanella, M. Padalino, V. Vida, G. Stellin, P. Lago, D. Trevisanuto ABS 10. INTRA-HOSPITAL TRANSPORTATION OF EXTREMELY PRETERM INFANTS AND INCIDENCE OF INTRAVENTRICULAR HAEMORRHAGES • N. Wadström, M. Breindahl, B. Hallberg, B. Skiöld ABS 11. RISK OF POSTNATAL TRANSPORT AND OUTCOME OF LATE PRETERM INFANTS BORN AT NON-TERTIARY CENTRES: A RETROSPECTIVE COHORT STUDY • N. Doglioni, L. Salmaso, P. Facchin, D. Trevisanuto ABS 12. COMPARING THREE METHODS OF THERAPEUTIC HYPOTHERMIA ON TRANSPORTATION: A SINGLE CENTRE CANADIAN EXPERIENCE • H. Zein, S. Thomas, K. Yusuf, S. Vayalthrikovil, R. Paul, S. Dossani, K. Kapores, K. Pearson-Mitchell, K. Mohammad ABS 13. USE OF TECOTHERM NEO TO MAINTAIN NORMOTHERMIA IN EXTREME PRETERM INFANTS DURING TRANSPORT AS A QUALITY IMPROVEMENT PROJECT • I. Fierens, P. Rusinga, L. Kelly, A. Iqbal, N. Ratnavel ABS 14. CARDIOPULMONARY POINT-OF-CARE ULTRASOUND (POCUS) IN THE NEONATAL TRANSPORTATION • W. Durlak, M. Jagła, K. Starzec, A. Grudzień, T. Tomasik, P. Błoński, P. Kwinta ABS 15. OUR EXPERIENCE IN NEONATAL AND PEDIATRIC TRANSPORT HIGH FIDELITY SIMULATION SCENARIOS • N. Torre, N. Millan, C. Alejandre, D. Vila, A. Olego, M.P. Larrosa, J.M. Quintilla, E. Esteban ABS 16. AN EVALUATION OF THE PRE-TRANSFER STABILISATION OF PRETERM INFANTS FOLLOWING PATENT DUCTUS ARTERIOSUS LIGATION BY THE LONDON NEONATAL TRANSFER SERVICE • C. Warrick, J. Ragasan, P. Rusinga, F. Barker ABS 17. THE NEONATAL INTENSIVE TRANSPORT TEAM IN UPPSALA, SWEDEN: A DESCRIPTION OF WORKING METHODS FROM A REGISTERED NURSE PERSPECTIVE • A. Backström, S. Fäldt ABS 18. PARTICIPANTS' EXPERIENCE IN NEONATAL AND PEDIATRIC TRANSPORT HIGH FIDELITY SIMULATION COURSE • N. Torre, N. Millan, C. Alejandre, D. Vila, A. Olego, M.P. Larrosa, J.M. Quintillá, E. Esteban ABS 19. SPECIFIC TRAINING ON NEONATAL TRANSPORT: THE SEM-PEDIATRIC VALL D'HEBRON COURSE • A. Gallardo, T. Esclapés, O. Rodríguez, L.L. Subirana, M.M. Pardo, R. Jordán, E. Castellarnau, P. Domínguez ABS 20. A TAILORED INHALED NITRIC OXIDE (iNO) THERAPY DEVICE IN CASES OF LOW ANNUAL USE IN NEONATAL EMERGENCY TRANSPORT • C. Bellini, L.A. Ramenghi ABS 21. TELEMEDICINE: A CHRISTCHURCH EXPERIENCE • A. Jackson ABS 22. PROVISION OF NASAL HIGH-FLOW THERAPY (HFT) USING VAPOTHERM® DEVICE FOR NON-INVASIVE RESPIRATORY SUPPORT DURING NEONATAL TRANSPORT • H. Ambulkar, A. Verma, J. Khanna, J. Mutch, A. Nichols, S. Pattnayak ABS 23. DESIGN OF A CHILD FRIENDLY PEDIATRIC AND NEONATAL AMBULANCE IN CATALONIA, SPAIN • M. Sardà, N. Torre, A. Olego, M.P. Larrosa, M. Hernández, M.J. Tovar, A. Llorens, O. Rodríguez, E. Esteban ABS 24. THE LUCY AIR AMBULANCE FOR CHILDREN PARENTAL EXPERIENCE • N. Cleave, C. Jackson ABS 25. CURRENT PARENT FEEDBACK RESPONSE RATES AND FEEDBACK METHODS IN THE NEONATAL TRANSPORT SERVICE ACROSS THE UK • P. Bhat, D. Winderbank-Scott, C. Garland, L. Watts, C. Leach, A. Frame, G. Bullimore, C. Lawn ABS 26. TABLET BASED FEEDBACK TO IMPROVE PARENT FEEDBACK RESPONSE RATES IN NEONATAL TRANSPORT - A QUALITY IMPROVEMENT STUDY • P. Bhat, C. Garland, A. Frame, G. Bullimore, L. Watts, C. Leach, C. Lawn ABS 27. FAMILY CENTRED CARE IN NEONATAL TRANSPORT • J. Weddell, A. Jackson, S. Davidson, N. Gupta ABS 28. BRAZILIAN REGULATION OF CHILDBIRTH IN TRANSPORT OF HIGH RISK INFANT IN A HOME CARE BIRTH SITUATION • C.V. Cupertino, S.A. Cupertino, A.V. Calado, J.J.S. Silva ABS 29. INFANTS REFERRED FOR THERAPEUTIC HYPOTHERMIA: QUALITY OF NEUROLOGICAL ASSESSMENT AND DOCUMENTATION • N. Goel, A. De Cunto, S. Mohinuddin, N. Ratnavel, M. Kumarasamy, A. Sinha ABS 30. COSYPOD - BRINGING BABIES BACK BETTER • J. Grant-Thomson ABS 31. BORN BEFORE ARRIVAL, BORN TOO SOON • R.A. Boland, P.G. Davis, J.A Dawson, M.A. Davey, L. William Doyle ABS 32. TRANSPORT RISK INDEX OF PHYSIOLOGIC STABILITY: A VALIDATION FOR SWEDISH CONDITIONS • B-M. Karlsson, J. Berg ABS 33. EVALUATION OF COST OF NEONATAL TRANSPORT ORGANIZATION IN LIGURIA REGION, ITALY • C. Bellini, M. Pasquarella, L. A. Ramenghi, D. Ambrosino, A.F. Sciomachen ABS 34. THE EFFECTS OF SHORT TERM WHOLE BODY VIBRATION, AS EXPERIENCED DURING NEONATAL AMBULANCE TRANSPORTATION, ON THE EARLY DEVELOPING RODENT BRAIN • L. Shipley, I. Bloor, D. Sharkey ABS 35. TRANSPORT RISK INDEX OF PHYSIOLOGICAL STABILITY (TRIPS): VALIDATING TRIPS FOR UK REGIONAL NEONATAL TRANSFER SERVICE • L. Sasidharan, S. Sampath, K. Patston, N. Ratnavel, A. Sinha, S. Mohinuddin, C. King ABS 36. PREDICTIVE MODEL TO ANTICIPATE THE NEED OF MAJOR MEDICAL INTERVENTIONS BY SPECIALIZED NEWBORN TRANSPORT TEAM • I. Marsinyach Ros, L. Sánchez García, M. Pérez Grande, A. Sánchez Torres, R. Mosqueda Peña, M.J. Rodríguez Castaño, D. Elorza Fernández ABS 37. QUALITY OF NEONATAL TRANSPORT PERFORMED BY A SPECIALISED COMBINED NEONATAL AND PEDIATRIC TRANSPORT UNIT IN CATALONIA (SPAIN) • O. Rodríguez, T. Esclapés, A. Gallardo, M. Pardo, L. Subirana, P. Domínguez ABS 38. MATERNAL ASSISTED TRANSPORT SYSTEM: HOW EFFECTIVE ARE WE? - COMPARISON BETWEEN NEW SOUTH WALES AND THE AUSTRALIAN CAPITAL TERRITORY AND NORTHERN LOMBARDY • M. Betti, E. Ferrario, P. Tagliabue, T. Fedeli, R. Tironi, R. Bellù, A. Pellegrino, P. Vergani ABS 39. IMPROVING MOBILISATION DECISION PROCESS USING A CALL HANDLING ALGORITHM • J. Samara, R. Paul, A. Elsharkawy, A. Abou Mehrem, S. Thomas ABS 40. CHALLENGES OF A NEONATAL EMERGENCY & TRANSPORT SERVICE IN CENTRAL HUNGARY • Zs. Somogyvari, A. Szell, A. Berenyi ABS 41. INTERHOSPITAL TRANSPORT OF PEDIATRIC PATIENTS IN DENMARK - A SURVEY OF CURRENT PRACTICE • K. Nystrup, P. Poorisrisak, M. Breindahl, P. Hallas